Primary Use of the TruePath Crossing Device for Infrainguinal Chronic Total Occlusions With Intravascular Ultrasound Evaluation. (October 2018) - Soga, Yoshimitsu; Nakamura, Miho; Hirose, Kaoru; Ito, Nobuhiro; Tomoi, Yusuke; Hiramori, Seiichi; Ando, Kenji
Purpose: To evaluate the use of the TruePath crossing device as the primary recanalization tool for infrainguinal chronic total occlusions (CTO).Methods: A retrospective analysis was conducted of 50 patients (mean age 75 years; 26 men) with 55 infrainguinal CTOs treated with the TruePath between March 2017 and September 2017 at a single center. The mean occlusion length was 138±55 mm, and femoropopliteal lesions accounted for 65% of the 55 lesions. The primary outcome measure was CTO crossing using the TruePath alone; secondary outcomes were assisted success (>50% lumen gain using the TruePath), device-related complications, and intraluminal crossing evaluated by intravascular ultrasound (IVUS).Results: Complete success was achieved in 33 (60%) of 55 lesions having a mean occlusion length of 145±72 mm. Among these, the true lumen crossing rate was 97% according to IVUS evaluation. Assisted success was achieved in 15 (68%) of the 22 failures. Complete/assisted success, in which the TruePath was thought to have contributed to CTO crossing, was attained in 48 (87%) of the 55 lesions. Three (5.5%) complications were observed: a perforation, an access-site hematoma, and acute occlusion; only the perforation was device related (1.8%). Multivariate analysis showed PACCS grade 4 (odds ratio 4.5, 95% confidence interval 1.33 to 15.5, p=0.02) was an independent predictor of TruePath failure.Conclusion: Primary use of the TruePath crossing device for infrainguinal CTOs demonstrated a satisfactory complete success rate and a high rate of IVUS-documented intraluminal crossing with few device-related complications. Severe calcification is an independent predictor of TruePath failure.